Pelatihan Bantuan Hidup Dasar bagi Guru Sekolah Menengah di Daerah Pesisir Pulau Lombok Nusa Tenggara Barat - Widiastuti, Ida Ayu Eka; Wahyu Sulistya Affarah; Bayu Tirta Dirja; Anom Josafat; Ida Bagus Alit; Vici Muhammad Akbar; Ni Putu Sasmita Lestari; Niko Citami (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Lombok Island, West Nusa Tenggara, is one of the best tourist destinations in Indonesia. One impact of this is increased activity on the beach and sea, which has the potential to cause emergency conditions and require immediate assistance. Equipping coastal communities with the ability to perform basic life support (BLS) is crucial, including for teachers. The purpose of this activity is to provide participants with knowledge and understanding of the principles of BLS assistance, and participants can provide BLS assistance if they encounter accident/injury victims in the water. This activity was held at the Nipah Community Health Center Hall, Malaka Village, Pemenang District, North Lombok, with a total of 22 high school teachers from Malaka Village participating. The activity was divided into six sessions: pre-test, material delivery, demonstration using mannequins, BLS skills training for participants, discussion and question-and-answer session, and concluded with a post-test. The success of this activity was seen from the increase in post-test scores compared to the pre-test, which was 33.3%. The average pre-test score was 69.55, increasing to 92.73. During the training session, participants enthusiastically practiced the BHD skills that had been previously demonstrated by the presenter and team. This activity needs to be continuously carried out for coastal communities in different locations and targets as an effort to increase the life expectancy for victims who experience respiratory arrest while carrying out activities at sea or on the coast.